2020
DOI: 10.1177/1049732320942147
|View full text |Cite
|
Sign up to set email alerts
|

“I Feel Abused by My Own Mind”: Themes of Control in Men’s Online Accounts of Living With Anxiety

Abstract: Men’s experiences with anxiety are under-researched and poorly understood. Existing research gives little indication of how men talk about anxiety in situ, and little is known about how men describe their experiences of anxiety. Online discussion forums provide an opportunity to conduct naturalistic observations of how men describe their experiences with anxiety without the influence of a researcher. Thematic analysis, informed by principles of discursive psychology, was used to examine 130 opening posts to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 77 publications
2
18
0
Order By: Relevance
“…These constructions might function also, for example, to communicate men's suffering. Indeed, such additional functions of opening posts within the current data set have been explored further in other studies (see, e.g., Drioli‐Phillips, Oxlad, Feo et al, 2020; Drioli‐Phillips, Oxlad, LeCouteur et al, 2021). Further, the recurrent orientation to age, work and family and the orientation towards deviance and normality might also be shaped by the community norms of the forum, rather than being representative of the performance of masculinity and anxiety more generally.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These constructions might function also, for example, to communicate men's suffering. Indeed, such additional functions of opening posts within the current data set have been explored further in other studies (see, e.g., Drioli‐Phillips, Oxlad, Feo et al, 2020; Drioli‐Phillips, Oxlad, LeCouteur et al, 2021). Further, the recurrent orientation to age, work and family and the orientation towards deviance and normality might also be shaped by the community norms of the forum, rather than being representative of the performance of masculinity and anxiety more generally.…”
Section: Discussionmentioning
confidence: 82%
“…One study (Gough, 2016), an investigation of an online depression forum, has investigated men's online talk about their mental health. To our knowledge, there exist only two studies (Drioli‐Phillips, Oxlad, Feo, et al, 2020; Drioli‐Phillips, Oxlad, LeCouteur, et al, 2021), which investigate men's experiences of anxiety. In the first of those studies, Drioli‐Phillips and colleagues examine how men orient to notions of control within their accounts of living with anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Establishing shared ground and trust within an all-male social group may be an effective way to encourage men to speak more directly and openly about their emotions and mental wellbeing. Research on men’s use of online forums to discuss sensitive issues has also suggested trust as an important factor in men’s delayed help-seeking in face-to-face contexts and as a facilitator of men’s disclosure and discussion of a range of topics, from depression ( Gough, 2016 ) and anxiety Drioli-Phillips et al (2020a) , Drioli-Phillips et al (2020b) , to body image and eating disorders ( Flynn and Stana, 2012 ). Indeed, it appears that establishing trust or “safe spaces” may be vital in a range of contexts, both homosocial and otherwise, to encourage men to engage with emotional topics and to disclose any mental health and wellbeing concerns.…”
Section: Resultsmentioning
confidence: 99%
“…For example, certain online environments like discussion forums can enable men to (anonymously) share their distress and receive support from peers with similar experiences e.g., depression, infertility (e.g., Gough, 2016 ; Hanna and Gough, 2016 ). In fact, recent research by Drioli-Phillips et al (2020a) , Drioli-Phillips et al (2020b) has examined how men talk to each other about anxiety online and highlights the importance of presenting credible accounts, with anxiety characterised as loss of control.…”
Section: Introductionmentioning
confidence: 99%
“…The current study extends these findings by illuminating that, despite feelings of fear and reluctance to seek help, men with CLV wanted others’ help. Understanding the paradox of men’s fears and desires for help might motivate service providers to engage men in gender-sensitive ways by asking about their CLV experiences ( Drioli-Philips et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%